A Sea Surface Height Perspective on El Niño Diversity, Ocean Energetics, and Energy Damping Rates. Issue 7 (6th April 2020) - Shi, Jian; Fedorov, Alexey V.; Hu, Shineng
Abstract: Ocean energetics is a useful framework for understanding El Niño–Southern Oscillation; however, its key element, available potential energy (APE), requires accurate ocean subsurface data that are hard to measure. Here, we describe a sea surface height‐based index, SSHI, that accurately captures APE variations and can be easily computed from satellite observations. Using SSHI, we obtain an observation‐based estimate of the APE damping timescale of approximately 1.7 years, slightly longer than previous ocean reanalysis‐based estimates. Furthermore, SSHI serves as an indicator for El Niño "flavors" while recording the relative strength of the thermocline feedback. SSHI captures a decadal shift in El Niño–Southern Oscillation properties in early 2000s, with a more tilted mean thermocline and weaker thermocline slope variations indicative of the "Central Pacific" El Niño type dominating the past two decades, whereas SSH averaged over the tropical Pacific (a proxy for upper‐ocean heat content) shows a significant rising trend over this time. Plain Language Summary: El Niño is the warm phase of a climate oscillation originating in the tropical Pacific typically referred to as the El Niño–Southern Oscillation. The maximum sea surface temperature anomaly of canonical El Niño, called Eastern Pacific (EP) El Niño, is located over the equatorial EP. In recent years, another type of El Niño has become more prominent with its maximum sea surface temperature anomaly over the equatorial Central Pacific (CP), termed CP El Niño. Scientists often use variations in the available potential energy (APE) of the tropical ocean to describe El Niño–Southern Oscillation. However, APE computation requires accurate ocean subsurface data. Here, we describe a sea surface height‐based index, SSHI, that accurately captures APE changes but can be easily computed from satellite observations. Negative SSHI indicates a flatter thermocline and an El Niño state. We show that larger negative SSHI values typically indicate EP events, while small negative values tend to coincide with CP events. Moreover, SSHI indicates a more tilted mean thermocline and weaker thermocline slope variations after the early 2000s, indicative of the dominant "Central Pacific" El Niño. Using SSHI, we obtain an observation‐based estimate of APE damping timescale at approximately 1.7 years. Key Points: A sea surface height index (SSHI) is introduced as a linear component of anomalous SSH squared and averaged over the tropical Pacific SSHI records thermocline variations, approximates ocean energetics in the tropical Pacific, and helps distinguish different El Niño types SSHI gives an estimate of the damping timescale of available potential energy in the tropical Pacific ocean of approximately 1.7 years